STATE AUTHORITY FOR HEALTH SERVICES FOR PATIENTS IN INDIGENT STATUS - Sari, Betty Yunita; Huda, Mokhamad Khoirul; Nugraheni, Ninis (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The objective of this research is to determine the legal framework regarding the role of the state in providing health services and to identify the legal safeguards available to impoverished individuals seeking healthcare in hospitals. This research employs normative juridical research methods, which involve a statutory and conceptual approach. The findings of this study indicate that the state's responsibility in fulfilling the right to health, as outlined in Law No. 17 of 2023 on Health and Law No. 24 on the Social Security Agency for Health (BPJS), lacks consistency in terms of the essence and substance of state responsibility. It has been demonstrated that there are still a significant number of economically disadvantaged individuals in Indonesia who qualify as recipients of contribution assistance (PBI). Additionally, patients are currently lacking legal protection in relation to their entitlement to receive services at a hospital, as stipulated in Article 189 of Law number 17. This refers to the state's obligation to ensure the right to health by offering sufficient and easily accessible healthcare facilities for all segments of the population. The state bears the primary obligation to ensure the fulfilment of its citizens' right to health as mandated by the constitution. States shall prioritise and ensure the realisation of the right to health without any kind of neglect or disregard.